Analisis Profitabilitas Pengembangan Usaha Ternak Itik Petelur di Kecamatan Banyubiru Kabupaten Semarang Jawa Tengah - Aditya Dwi Mulyono; Wulan Sumekar; Dwi Sunarti (Politeknik Negeri Jember, 2017)
The purpose of this study is to know the profitability of laying ducks farm in Banyubiru Subdistrict, Semarang Regency, Central Java Province. This research were collected using 59 respondents was conducted survey method. The results showed that the average ducks farmers in District Banyubiru maintained 116 ducks. Average monthly income of farmers IDR 1.917.808,00. Profitability laying ducks farming business is shown by Net Profit Margin value of 42.74%, ROI of 26.54%, and Cost-Profit Ratio of 74.63%.